Factors associated with perceived quality of life among breast cancer patients during treatment at National Cancer Institute, Putrajaya, Malaysia - Ng, Krystal Lu Shin (2019)
Breast cancer remains as the main cause of death among female worldwide. In light of its good prediction on survival of cancer, perceived quality of life (QoL) has been increasingly recognized as an important clinical outcome for oncology patients. This study aimed to determine the perceived QoL as well as its determinants among breast cancer patients during treatment.